4x-9=3.5x

Simple and best practice solution for 4x-9=3.5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-9=3.5x equation:


Simplifying
4x + -9 = 3.5x

Reorder the terms:
-9 + 4x = 3.5x

Solving
-9 + 4x = 3.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3.5x' to each side of the equation.
-9 + 4x + -3.5x = 3.5x + -3.5x

Combine like terms: 4x + -3.5x = 0.5x
-9 + 0.5x = 3.5x + -3.5x

Combine like terms: 3.5x + -3.5x = 0.0
-9 + 0.5x = 0.0

Add '9' to each side of the equation.
-9 + 9 + 0.5x = 0.0 + 9

Combine like terms: -9 + 9 = 0
0 + 0.5x = 0.0 + 9
0.5x = 0.0 + 9

Combine like terms: 0.0 + 9 = 9
0.5x = 9

Divide each side by '0.5'.
x = 18

Simplifying
x = 18

See similar equations:

| 7(-4x+7)=-7 | | 7=-x+3y | | 1/5=m/30 | | 20(v+4)-4v=4(4v+2)-11 | | 124=4x+-10y | | 2x+x+5-5=6 | | 4(p-6q)=0 | | -20=5(3x-10)-5x | | 118=8(1+7n)-2 | | 1/5x=x | | 8(3-5a)=-296 | | 7x^(2/3)-63=0 | | 3/7b=9 | | 14+c=39 | | 22/25X15/52X8/33 | | 8(3-5a)=-188 | | 5(-3x+5)=6-4x | | 27x-19-39x=-65 | | -3(2x+3)=6x+9 | | -0.1x+1.25=-0.5x+4.45 | | 8-9t=21r-17 | | (6+y)(2y+3)=0 | | 6p-16p=70 | | 3w+2-w=-3 | | 45x-21-17x=-63 | | 84=2k-5(2k-4) | | 3(x-1)+41=x-7(x+1) | | 6(4T+1)-13=T-(T+6) | | 6x+16=-2+8x | | 24x-81+7x=19 | | 25+10(12-x)=(2x-7) | | 84=-6(6+5x) |

Equations solver categories